Effect of Combined Tempering and Aging in the Austenite Reversion, Precipitation, and Tensile Properties of an Additively Manufactured Maraging 300 Steel - Conde, Fábio Faria; Escobar, Julian David; Rodriguez, Johnnatan; Afonso, Conrado Ramos Moreira; Oliveira, Marcelo Falcão; Avila, Julian Arnaldo [UNESP] (Springer Nature, 2021)
Maraging 300 is an ultrahigh strength steel with significant alloy addition, resulting in a martensitic matrix hardened by precipitation through aging treatment. In these steels, intercritical tempering can provide reverted austenite and precipitation of intermetallic products, increasing the ductility of additively manufactured parts due to austenite presence. Studies deal with postprocessing of additive manufactured parts of maraging steel; however, few focused on phases evolution during the heat treatments and their mechanical response. In the present work, a maraging 300 steel processed by laser-based powder-bed fusion was studied with a focus on microstructural and mechanical properties after applying several postprocessing heat treatments. Tensile tests assessed the mechanical properties, and the microstructure was analyzed by scanning and transmission electron microscopy. A synchrotron beamline with x-ray diffraction was used to conduct in situ measurements of martensite and austenite evolution. The in situ phase evolution revealed that isothermal heat treatments were efficient in promoting martensite-to-austenite reversion. Likewise, the presence of austenite significantly enhanced the ductility, however, at some mechanical strength expense.
Keywords: additive manufacturing; austenite reversion; laser powder-bed fusion; maraging 300; mechanical properties; x-ray measurements